2009
DOI: 10.1007/978-3-642-02574-7_63
|View full text |Cite
|
Sign up to set email alerts
|

Aesthetics in Human-Computer Interaction: Views and Reviews

Abstract: Abstract. There is a growing interest of aesthetics issues in Human Computer Interaction (HCI) in the recent days. In this article we present our literature review where we investigate where and how aesthetics has been addressed by the HCI researchers. Our objective is to find out the sectors in HCI where aesthetics has a role to play. Aesthetics in HCI can be the common interest that involves both art and technology in HCI research with a view to facilitate from each others discipline in the form of mutual in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 35 publications
0
14
0
2
Order By: Relevance
“…Moreover, adaptation within user interfaces has been shown to lead into higher ratings in look and feel as well as long-term usage of platforms (Debevc et al 1996;Hartmann et al 2007;Sarsam and Al-Samarraie 2018). This reflects the well-established knowledge in product design and marketing: aesthetics matter (e.g., Hartmann et al 2007;Tractinsky et al 2000), and collaboration between artists and technologists is essential in this regard (Ahmed et al 2009). Increasing demands for customization within human-computer interaction introduce new possibilities and challenges to designers, which justifies further research on the topic.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Moreover, adaptation within user interfaces has been shown to lead into higher ratings in look and feel as well as long-term usage of platforms (Debevc et al 1996;Hartmann et al 2007;Sarsam and Al-Samarraie 2018). This reflects the well-established knowledge in product design and marketing: aesthetics matter (e.g., Hartmann et al 2007;Tractinsky et al 2000), and collaboration between artists and technologists is essential in this regard (Ahmed et al 2009). Increasing demands for customization within human-computer interaction introduce new possibilities and challenges to designers, which justifies further research on the topic.…”
Section: Introductionmentioning
confidence: 77%
“…Aesthetics considerations in computers and other devices have quickly started to garner attention as the means to positively affect usability and satisfaction (Ahmed et al 2009;Maity et al 2015Maity et al , 2016Norman 2004;Tractinsky et al 2000). Studies have shown that a user interface with balanced elements promotes user engagement, while a cluttered interface may result in frustration (Jankowski et al 2016(Jankowski et al , 2019Lee and Boling 1999;Ngo et al 2000;Salimun et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The meaning and the deeper relation of the link between information theory and aesthetic are to be further investigated in future work. Finding the most fundamental law or the optimization process that underlies aesthetically appealing patterns would be of great interest for the research in this area and for many applications [ 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ]. It is interesting to see whether the proposed approach has any link to the aesthetic judgment mechanism in the brain, and how is that related to information theory.…”
Section: Discussionmentioning
confidence: 99%
“…With a purely procedural, quantitative influence the balance has dipped away from 'aesthetic pleasure' towards functionalism and usability. In doing so aesthetics has been viewed as 'inversely proportional' to usability (Ahmed et al, 2009). One of the issues with different disciplines, especially with a quantitative/qualitative divide, is agreeing what constitutes knowledge, methodology and axioms.…”
Section: Moggridge Wanted the New Discipline Tomentioning
confidence: 99%